EFFECTIVENESS OF PUBLIC POLICIES AND QUILOMBOLA ENTREPRENEURSHIP: THE ROLE OF SOCIAL TECHNOLOGIES IN THE VILLAGE OF TABACARIA (AL) - Ricardo Pereira Accioly, Sérgio; David Cohen, Eric; Santos do Nascimento, Marielza; Estanislau de Oliveira Neto , Antonio (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes the effectiveness of public policies aimed at fostering entrepreneurship in Quilombola communities, emphasizing the role of social technologies as mediating mechanisms between institutional design and territorial realities. The study adopts a qualitative and exploratory approach, using a case study design focused on the Tabacaria community, located in Palmeira dos Índios, Alagoas, Brazil. Methodologically, the research is based on documentary analysis and a systematic literature review, supported by secondary data from official sources and academic studies. The findings reveal a significant gap between the normative formulation of the Brazilian Quilombola Program (PBQ) and its implementation in local contexts, characterized by institutional limitations, low policy reach, and weak intergovernmental coordination. In this scenario, social technologies emerge as strategic tools capable of enhancing policy effectiveness by promoting participatory, context-sensitive, and community-driven solutions. The study contributes theoretically by framing social technologies as mediating devices of policy effectiveness in vulnerable contexts, advancing discussions on social innovation and territorial development. From a practical perspective, the results highlight the need to redesign public policy implementation strategies, strengthening participatory governance and local engagement.